2019
DOI: 10.1038/s41586-019-1685-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for enzymatic photocatalysis in chlorophyll biosynthesis

Abstract: The enzyme protochlorophyllide oxidoreductase (POR) catalyses a lightdependent step in chlorophyll biosynthesis that is essential to photosynthesis and ultimately all life on Earth. 1-3 POR, which is one of three known light-dependent enzymes, 4,5 catalyzes reduction of the photosensitizer and substrate protochlorophyllide to form the pigment chlorophyllide. Despite its biological importance, a structural basis for POR photocatalysis has remained elusive. Here, we report crystal structures of cyanobacterial PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
193
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(206 citation statements)
references
References 28 publications
12
193
0
1
Order By: Relevance
“…Nature has discovered two completely different ways to achieve this reduction: in one, a lightdependent reaction is catalyzed by NADPH:protochlorophyllide oxidoreductase (LPOR; EC 1.3.1.33) (207,208); in the other, reduction of the C17-C18 double bond is catalyzed by a dark-operative protochlorophyllide reductase (DPOR), consisting of ChlL, ChlN and ChlB subunits that display similarity to the components of nitrogenase (209). The ability to trigger the catalytic cycle with short pulses of light has led to a number of kinetic studies (210)(211)(212), and recently the structure of LPOR has been reported (208). The phylogenetic distribution of LPOR and DPOR is interesting; anoxygenic photosynthetic bacteria contain only DPOR; cyanobacteria, green algae, mosses and most gymnosperms possess both LPOR and DPOR; and angiosperms (flowering plants) contain only LPOR.…”
Section: The Transformation Of Protoix Into Chls -Chl Amentioning
confidence: 99%
“…Nature has discovered two completely different ways to achieve this reduction: in one, a lightdependent reaction is catalyzed by NADPH:protochlorophyllide oxidoreductase (LPOR; EC 1.3.1.33) (207,208); in the other, reduction of the C17-C18 double bond is catalyzed by a dark-operative protochlorophyllide reductase (DPOR), consisting of ChlL, ChlN and ChlB subunits that display similarity to the components of nitrogenase (209). The ability to trigger the catalytic cycle with short pulses of light has led to a number of kinetic studies (210)(211)(212), and recently the structure of LPOR has been reported (208). The phylogenetic distribution of LPOR and DPOR is interesting; anoxygenic photosynthetic bacteria contain only DPOR; cyanobacteria, green algae, mosses and most gymnosperms possess both LPOR and DPOR; and angiosperms (flowering plants) contain only LPOR.…”
Section: The Transformation Of Protoix Into Chls -Chl Amentioning
confidence: 99%
“…Interestingly, these positions are not the amino acids responsible for direct NADPH binding as deduced from the recently published crystal structure from Synechocystis. [27] As selected enzymes, which are in nature not light-dependent, have been shown to possess promiscuous activity under the influence of light, [28][29] LPORs as NADPH-dependent natural photoenzymes may be targets for further studies of light dependent reactions.…”
Section: Discussionmentioning
confidence: 99%
“…When locating the corresponding amino acids identified above in the recently published crystal structures [27] of the LPORs from T. elongatus (PDB: 6R46) and Synechocytis (PDB: 6R48) it becomes clear that these three amino acids are not amino acids in close contact with the phosphate moiety of the NADPH or even the cofactor itself (Figure 7). The amino acids are in an α-helix next to the NADPH cofactor, but the distance between the amino acids and the NADPH are too long for an obvious interaction.…”
Section: Nadh/nadph Cofactor Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…POR is a light dependent key enzyme required for chlorophyll biosynthesis by catalyzing protochlorophyllide to chlorophyllide (41,42). It has been reported that POR is crucial for plant growth and development since nonfunctional plants displayed reduced chlorophyll content and severe photoautotrophic growth defects (43,44). The expression level of POR is lower in albino mutant than in wild type, indicating that albino mutant might be incapable in chlorophyll biosynthesis.…”
Section: Discussionmentioning
confidence: 99%